MODEL KEPEMIMPINAN SPIRITUAL DALAM MENINGKATKAN KUALITAS SUMBER DAYA PENDIDIK: (Studi Kasus di SMPN 1 Temayang, Bojonegoro) - Sri Minarti; EKA (Pendidikan Agama Islam, 2021)
This paper focuses on the spiritual leadership model, the principal of model is motivating, sharing, loving, being an example, and being a learner, in the end, it is expected to be able to improve the quality of educator resources (teachers) to be productive and learners. To understand the phenomenon of the principal's leadership model, with a qualitative approach of case study type, and interactive data analysis as suggested by Miles and Hubemann. This study concludes that the spiritual leadership model is able to foster a spirit of achievement, hard work, tenacity and minimize laziness and open insight to not easily complain or get discouraged, because of the growing awareness that after efforts, the final result is left to the Creator. With the awareness possessed by teachers, self-confidence and willingness to learn will grow in order to be able to present the best (productive) work in carrying out their duties.